Access security in CDMA2000, including a comparison with UMTS access security. - Rose, G. (IEEE Wireless communications)
One of the principal 3G systems developed is the CDMA2000 cellular mobile communications system. Like its UMTS 3G cousin, CDMA2000 is also based on an existing system core. This article gives a description of the access security mechanisms found in CDMA2000. Access security in 3G systems face many of the same design challenges and constraints. It is therefore no surprise that many aspects and features are shared between CDMA2000 and UMTS. The article will therefore also compare and contrast the approaches to access security taken in the CDMA2000 and UMTS systems.